(untitled) (New York, 1995)
Van Nostrand's covers the six general areas of earth and space sciences, life sciences, energy and environmental science, materials science, physics and chemistry, and mathematics and information sciences. Where appropriate, entries have an identifying tag (e.g., Bond [Chemical]). The length of entries varies from one sentence (Aeolian Tones) to 11 pages (Climate). Only the longer entries are signed by their authors and have appended reading lists. The entries appear to be current. For example, Jupiter mentions the Ulysses satellite flyby of the planet in 1992, and 13 new readings have been added to its bibliography. Telescope has been expanded from 8 to 12 pages, has several new illustrations, and its bibliography is twice as long. This entry mentions the 1993 corrections to the Hubble Space Telescope. Similarly, the coverage under Television has been expanded to include a discussion of high-definition television, with mention of developments as recent as 1994. This work does not contain any biographies. Information on symbols and mathematical conversions is found under Units and Standards. This encyclopedia has a good history of revision. A comparison with the previous edition shows that about 200 new pages have been added to the text. There are approximately 7,300 entries, an increase of several hundred. Throughout the text are many appropriately placed black-and-white photographs, line drawings, tables, charts, and diagrams. In the past this work has been criticized for the quality of its illustrations. There are several instances in this new edition of attempts to improve the contrast and size of photographs.
Keywords: Science,Engineering; Encyclopedias,Encyclopedias